MAVEN and MEX Multi‐instrument Study of the Dayside of the Martian Induced Magnetospheric Structure Revealed by Pressure Analyses. Issue 11 (8th November 2019) - Holmberg, M. K. G.; André, N.; Garnier, P.; Modolo, R.; Andersson, L.; Halekas, J.; Mazelle, C.; Steckiewicz, M.; Génot, V.; Fedorov, A.; Barabash, S.; Mitchell, D. L.
Abstract: A combination of statistical studies and 18 case studies have been used to investigate the structure of the induced Martian magnetosphere. The different plasma and magnetic pressure forces on the dayside of the induced magnetosphere of Mars have been studied using 3.5 years of Mars Atmosphere and Volatile Evolution (MAVEN) and Mars Express (MEX) observations. We present estimates of typical values for the dominant pressure terms, that is, the thermal pressures of the ionosphere and the magnetosheath, the magnetic pressure of the magnetic pile‐up region, and the solar wind dynamic pressure. For 18 typical orbits the altitudes and relative distances of the pressure balance boundaries, the photoelectron boundary, the ion composition boundary, and the induced magnetosphere boundary are estimated. The magnetic pile‐up boundary is discussed but not further studied since earlier characterizations of the magnetic pile‐up boundary do not agree with our results. This study focuses on the transition region between the ionosphere and the magnetosheath on the dayside of Mars. We show that earlier definitions of the photoelectron boundary, ion composition boundary, and induced magnetosphere boundary do not characterize the transition region well, mainly because each boundary is based on measurements from only one or two instruments. In order to characterize the transition region correctly, changes in magnetic field strength and fluctuations, dominant ion species, electron and ion densities and energy distributions need to be considered. This article confirms a complex interaction between Mars and the solar wind and can explain why previous studies have had difficulties to describe the force balance. Key Points: This article presents an overview of the Martian dayside magnetospheric structure based on the dominant pressure terms Typical altitudes of the pressure balance boundaries, the PEB, ICB, and IMB are provided We show that earlier defined boundaries are not a sufficient characterization of the ionosphere/magnetosheath transition region